Find the right mutual funds : - Breyfogle, Forrest W. (Wiley, 2001)
This book is a unique blend of practical knowledge and cultural change, revolution and evolution strategies. I recommend that serious managers buy the book, spend some serious time reading, and then go out and use its lessons to make a name for themselves."-William Baker, Benchmarking/Knowledge Transfer Office, Raytheon Corporation "I believe Managing Six Sigma will be the new reference standard for the quality movement in coming years."-Robert T. Hunter, Executive Vice President, Rehnborg Center for Nutrition and Wellness